Der Postpunktionskopfschmerz: Klinik, Diagnostik und aktuelle Therapieoptionen = Postdural puncture headache-clinics, diagnostics and current therapy options - Siegler, Benedikt Hermann; Kranke, Peter; Neef, Vanessa (Anästhesiologie & Intensivmedizin, 2025)
The present review focuses on post dural puncture headache (PDPH) as a complication after epidural or spinal anaesthesia, especially in an obstetric context. The pathophysiology of PDPH is complex and not yet fully understood. However, CSF loss and meningeal irritation seem to play a central role. The incidence varies widely and depends on patient and procedure related risk factors. Symptoms of PDPH are typically positional, with frontooccipital head ache that can be supplemented by neck stiffness, tinnitus, and photophobia. The therapy of PDPH includes con servative measures such as hydration and pharmacotherapy with analgesics and caffeine. The epidural blood patch (EBP) is considered the therapeutic gold standard, although the optimal time of application is controversial. Alternative therapies such as occipital nerve blocks, blocks of the sphenopalatine ganglion and epidural fibrin patches offer additional options, especially in the case of contraindications to EBP.